Responsible research and innovation key performance indicators in industry: A case study in the ICT domain. Issue 2 (1st May 2018) - Yaghmaei, Emad
Abstract : Purpose: Responsible research and innovation (RRI) is taking a role in assisting all types of stakeholders, including industry members, in moving their research and innovation (R&I) initiatives to tackle grand challenges. The literature on RRI, however, focuses little on how industry can implement RRI principles. To solve this gap, the purpose of this study is to construct a conceptual framework for managing and assessing RRI principles in the industry. Design/methodology/approach: Qualitative research was used to build the RRI key performance indicator list; 30 interviews were conducted to design a framework which was pilot tested in a company to identify how to align technology outcomes to the values, needs and expectations of the society. Findings: This study depicts five successive RRI implementation levels and exhibits RRI key performance indicators. Drawing on extant models, this study develops RRI levels and indicators to discuss why industry should become engaged in RRI, how it can embed RRI principles into R&I processes and how RRI indicators can be managed systematically. Originality/value: The connection between RRI key performance indicators and RRI levels determines how industry can integrate principles and methodologies of RRI into R&I processes. The model in the study shows how companies move from one RRI stage to another and this study aims to exhibit an ideal stage of RRI for industry.